2005
DOI: 10.1021/jf050496+
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Phytoalexin Resveratrol (3,5,4‘-Trihydroxystilbene) in Peanuts and Pistachios by High-Performance Liquid Chromatographic Diode Array (HPLC-DAD) and Gas Chromatography−Mass Spectrometry (GC-MS)

Abstract: The phytoalexin resveratrol (3,5,4'-trihydroxystilbene) in edible peanut (Arachis hypogaea L.) and pistachio (Pistacia vera L.) varieties grown in Turkey was analyzed by high-performance liquid chromatographic diode array and gas chromatography-mass spectrometric detection. trans-Resveratrol in six peanut varieties, five pistachio varieties, and four market samples ranged between 0.03 and 1.92 microg/g. The Cerezlik 5025 peanut (1.92 +/- 0.01 microg/g) and Ohadi pistachio genotype (1.67 +/- 0.01 microg/g) had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
95
3
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(101 citation statements)
references
References 21 publications
0
95
3
3
Order By: Relevance
“…§ Data from Yang et al (142) . k Data from Tokuşoglu et al (143) . { Data from Blomhoff et al (144) .…”
Section: Introductionmentioning
confidence: 99%
“…§ Data from Yang et al (142) . k Data from Tokuşoglu et al (143) . { Data from Blomhoff et al (144) .…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol (3, 5, 4′-trihydroxystilbene) is one of the major stilbene phytoalexin produced by a wide variety of plants in response to stress, injury, ultraviolet (UV) irradiation, and fungal (e.g., Botrytis cinerea) infection (Burns et al 2002) There are numerous reports on resveratrol content of grapes (Vitis vinifera) (Pezzuto 2008). peanuts (Arachis hypogaea) (Tokusoglu et al 2005), berries (Rimando et al 2004) and legumes (Duenas et al 2006). While these plants have been reported as the primary dietary sources of resveratrol, several other sources have also been identified, including Itadori tea (from the root of Polygonum cuspidatum) (Vastano et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Among the antioxidants, phenolic compounds have attracted a particular interest since foods containing varying amounts and forms of these compounds show different antioxidant potentials. Recently, studies related to the antioxidant potential of nuts such as hazelnuts, walnuts and pistachios showed that these foods are good sources of antioxidant phenolic compounds (Fukuda et al, 2003;Kornsteiner et al, 2006;Tokuş oglu et al, 2005;Yurttas et al, 2000;Anderson et al, 2001;Gunduc and El, 2003). The clinical studies suggested that the supplementation of human diet with hazelnuts, walnuts or pistachios is beneficial for the amelioration of blood plasma antioxidant potential and lipid profiles that are closely related to cardiovascular risks (Edwards et al, 1999;Durak et al, 1999;Tapsell et al, 2004;Koçyigit et al, 2006;Lavedrine et al, 1999).…”
Section: Introductionmentioning
confidence: 99%